Multistability, phase diagrams and statistical properties of the kicked rotor: A map with many coexisting attractors - Martins L.C.* (2008)
We investigate the prevalence of multistability in the parameter space of the kicked rotor map. We report high-resolution phase diagrams showing how the density of attractors and the density of periods vary as a function of both model parameters. Our diagrams illustrate density variations that exist when moving between the familiar conservative and strongly dissipative limits of the map. We find the kicked rotor to contain multistability regions with more than 400 coexisting attractors. This fact makes the rotor a promising high-complexity local unit to investigate synchronization in networks of chaotic maps, in both regular and complex topologies. © 2008 World Scientific Publishing Company.